Profiling of pathogenic variants in Japanese patients with sarcoglycanopathy - Rui Shimazaki; Yoshihiko Saito; Tomonari Awaya; Narihiro Minami; Ryo Kurosawa; Motoyasu Hosokawa; Hiroaki Ohara; Shinichiro Hayashi; Akihide Takeuchi; Masatoshi Hagiwara; Yukiko K. Hayashi; Satoru Noguchi; et al. (Orphanet Journal of Rare Diseases)
Abstract Background Sarcoglycanopathies (SGPs) are limb-girdle muscular dystrophies (LGMDs) that can be classified into four types, LGMDR3, LGMDR4, LGMDR5, and LGMDR6, caused by mutations in the genes, SGCA, SGCB, SGCG, and SGCD, respectively. SGPs are relatively rare in Japan. This study aims to profile the genetic variants that cause SGPs in Japanese patients. Methods Clinical course and pathological findings were retrospectively reviewed in Japanese patients with SGP. Genetic analyses were performed using a combination of targeted resequencing with a hereditary muscle disease panel, whole genome sequencing, multiplex ligation-dependent probe amplification, and long-read sequencing. The structures of transcripts with aberrant splicing were also determined by RT-PCR, RNA-seq, and in silico prediction. Results We identified biallelic variants in SGC genes in 53 families, including three families with LGMDR6, which had not been identified in Japan so far. SGCA was the most common causative gene, accounting for 56% of cases, followed by SGCG, SGCB, and SGCD, at 17%, 21%, and 6%, respectively. Missense variants in SGCA were very frequent at 78.3%, while they were relatively rare in SGCB, SGCG, and SGCD at 11.1%, 18.2%, and 16.6%, respectively. We also analyzed the haplotypes of alleles carrying three variants found in multiple cases: c.229C > T in SGCA, c.325C > T in SGCB, and exon 6 deletion in SGCG; two distinct haplotypes were found for c.229C > T in SGCA, while each of the latter two variants was on single haplotypes. Conclusions We present genetic profiles of Japanese patients with SGPs. Haplotype analysis indicated common ancestors of frequent variants. Our findings will support genetic diagnosis and gene therapy.